Case report: Surgical repair of congenitally corrected transposition of the great arteries with the guidance of three-dimensional printing - Zhang, Yanchun; Li, Yongnan; Ma, YuMei; Wei, Yalin; He, Fengxiao; Zhu, Yilin; Lu, Weixin; Zhao, Yinglu; Wu, Xiangyang (Frontiers in Cardiovascular Medicine, 2023)
A 10-year-old girl presented with obvious cyanosis, and saturation of arterial blood oxygen (SpO2) was decreased to 60.5% in the out-patient examination. Computed tomography angiography and echocardiography suggested congenitally corrected transposition of the great arteries (ccTGA), membranous ventricular septal aneurysm (MVSA), atrial septal defect (ASD), severe pulmonary stenosis (PS) and severe tricuspid regurgitation. Due to the complex pathological anatomical structures, the 3-dimensional printed model was used for preoperative assessment. After comprehensive evaluation completed, the operation was performed by physiological correction under cardiopulmonary bypass, including resection of MVSA, repair using bovine pericardial patch for ASD, and linear valvuloplasty of tricuspid valve. Due to the special anatomical structures of ccTGA, PS was treated by extracardiac pipe technique. After the operation, the patient recovered well and cyanosis disappeared, SpO2 was up to 96%, and the extracardiac pipe was well-functioning without regurgitation or obstruction.